Rancang Bangun Running Text Menggunakan Modul Led Matrix P10 Berbasis Arduino Uno Di Fakultas Teknik Universitas Pgri Banyuwangi - malik yuhanas; Charis Fathul Hadi; Risk Fita Lestari (ZETROEM, 2021)
Abstract - Running text or commonly known as running text is a medium for delivering information that we often encounter in public places, both in places of worship, shopping centers and shops because it is informative. Running text one of the digital electronic media in the form of an information board designed from several LEDs and arranged in a matrix to display text. Currently, most text writing relies on a computer unit or via Bluetooth on an android smartphone which has limitations in terms of distance and is less efficient. The stage of making the tool uses the ESP8266 module, Arduino Uno AtMega 328 as the control center on the display information board, RTC DS3231 as a timer to display the hour, day, date, month, and year which will be displayed on the running text. Then to input text information using an android smartphone application with a wifi connection, then the text is received by the ESP8266 module which is forwarded to the Arduino UNO AtMega 328 to be displayed on running text which can be in the form of letters, numbers, and punctuation marks. Through this running text design, it is hoped that the information delivery system at the Faculty of Engineering, PGRI Banyuwangi University, is more effective and efficient, the process of changing the text can be done at any time and the process of changing the running text data becomes easier. The running text uses a P10 type LED matrix with a size of 96x32 cm. Keywords — Running text, Arduino Uno AtMega 328, ESP8266, Modul LED Matrix P10